Fluorocitrate and neurotropin confer analgesic effects on neuropathic pain in diabetic rats via inhibition of astrocyte activation in the periaqueductal gray. (18th January 2022) - Liu, Xingfeng; He, Jingxin; Gao, Jie; Xiao, Zhi
Highlights: Astrocyte activation in the vlPAG in DNP rats. Fluorocitrate and neurotropin inhibit the astrocyte activation in the vlPAG. Fluorocitrate and neurotropin produce analgesic effects on DNP rats. Abstract: Currently, effective treatments for diabetic neuropathic pain (DNP) are still unmet clinical needs. Activation of astrocytes in the ventrolateral region of periaqueductal gray (vlPAG) has a regulating effect on pain responses. The present study was designed to confirm that repeated intra-vlPAG injection of fluorocitrate (FC), a selective inhibitor of astrocyte activation or intraperitoneal (IP) injection of neurotropin, a widely prescribed analgesic drug for chronic pain, inhibited the activation of astrocytes in vlPAG and thus produced an analgesic effect on DNP. An in vivo model was developed to study DNP in rats. The changes in mechanical withdrawal threshold (MWT) and activation levels of astrocytes in the vlPAG were evaluated in all experimental rats. Compared with normal rats, vlPAG-based glial fibrillary acid protein (GFAP) was clearly upregulated, whereas the MWTs of DNP rats were markedly diminished. The intra-vlPAG injections of FC or IP injections of neurotropin attenuated the alterations both in MWTs and expression levels of GFAP in vlPAG in DNP rats. Collectively, these findings suggest the antinociceptive effects of FC and neurotropin in DNP rats, which were associated with suppressing the activation of astrocytes in vlPAG.